Empirical study on the usage of cash flow statement as a tool to predict company financial distress / Shariful Amran Abd Rahman and Ruslaina Yusoff - Abd Rahman, Shariful Amran; Yusoff, Ruslaina (2004)
This study was carried out to examine whether cash flow can be a good predictor to debt restructuring companies. Sixty companies of Bursa Malaysia (MSE) have been identified as a sample in the current study. Thirty companies were classified as PN4 and another 30 matching companies were classified as non-debt restructuring companies. The classification was done in order to determine the differences between cash flow related ratios such as cash flow changes, cash flow over total debt, cash flow over total assets, cash flow over current liabilities and cash flow per share issued. The study hypothesized that the means for the cash flow based ratios have no significant difference between debt restructuring and non-debt restructuring companies.